Samuel D. Schenk correspondence - Schenk, Samuel D.
ALS (1863 August 5) to Schenk while serving with the 173rd Pennsylvania Infantry Regiment, Co. A., from his wife, Anna M. Schenk, relating to the Union cause, military affairs, and family matters.
Union soldier.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Schenk, Anna M. -- Correspondence; Schenk family; United States. -- Army. -- Pennsylvania Infantry Regiment, 173rd (1862-1863). -- Company A; Pennsylvania -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; Soldiers